Is arterial pressure a determinant of renal prostaglandin release? - Ehmke, Heimo; Persson, Pontus B.; Hackenthal, Eberhard; Schweer, Horst; Seyberth, Hannsjörg W.; Kirchheim, Hartmut (American journal of physiology. Regulatory, integrative and comparative physiology, 1993)
The effect of changes in renal perfusion pressure (RPP) on renal prostaglandin (PG) release was investigated in conscious dogs (n = 10). PGE2, PGF2 alpha, and 6-keto-PGF1 alpha levels in renal venous and aortic plasma were measured in response to controlled reductions of RPP by an inflatable cuff implanted around the renal artery. PG plasma concentrations were determined by gas chromatography-negative ion chemical ionization mass spectrometry. At control RPP, PGE2 and PGF2 alpha concentrations in renal venous plasma were severalfold higher than in aortic plasma (PGE2, 54.2 +/- 13.4 vs. 9.3 +/- 2.7 pg/ml, P < 0.01; PGF2 alpha, 40.3 +/- 10.4 vs. 10.4 +/- 3.4 pg/ml, P < 0.01), whereas only a small secretion rate was found for 6-keto-PGF1 alpha (renal vein, 24.3 +/- 2.6 pg/ml; aorta, 17.4 +/- 3.4 pg/ml; P < 0.01). Concentrations of all three PGs in renal venous or aortic plasma did not change in response to reductions of RPP within the normal range of renal blood flow (RBF) autoregulation. The mean difference between PG release at a RPP of 70 mmHg and control was for PGE2 -7.9 pg/ml with a 95% confidence interval (CI) from -20.7 to + 5.0 pg/ml; for PGF2 alpha it was -13.7 pg/ml (95% CI -29.4 to +2.0 pg/ml); and for 6-keto-PGF1 alpha it was -0.9 pg/ml (95% CI -6.0 to +4.1 pg/ml). Reductions of RPP below the lower limit of RBF autoregulation (< 66 mmHg) had no effect on 6-keto-PGF1 alpha secretion rate but decreased secretion rates of PGE2 and PGF2 alpha (n = 4).(ABSTRACT TRUNCATED AT 250 WORDS)
Gesehen am 04.12.2024